"We still keep our culture to stay alive": acculturation and adaptation among resettled young adult refugees from Burma. Issue 2 (4th March 2022) - Tonui, Betty C.; Mitschke, Diane B.
ABSTRACT: Coming of age as a recently resettled refugee from Burma poses unique opportunities and challenges in navigating dissimilar norms and expectations of family, culture, and the new host environment. Understanding these experiences and how they are interpreted by young adults can provide insight into the mechanisms through which this segment of the resettled refugee community can be supported and encouraged. The present study used semi-structured interviews to gain insight into the resettlement experiences of refugee young adults from Burma. The sample consisted of 14 Karen young adult refugees from Burma who had been resettled to a large urban city in the southwestern United States for at least 5 years. Data analysis revealed five major themes: (1) cultural pride; (2) filial obligation; (3) community commitment; (4) contrast; and (5) resettlement challenges. In sum, the young adult participants in this study had positive outlooks about their circumstances and were forward-thinking in their aspirations, particularly as they related to educational and career goals. Participants emphasized the importance of maintaining cultural traditions and ethnic community connections throughout the resettlement experience as a mechanism through which challenges and obstacles can be overcome.